PERLINDUNGAN HUKUM PADA KORBAN TINDAK PIDANA LINGKUNGAN HIDUP MELALUI MEDIASI PENAL DALAM PERSPEKTIF PEMBARUAN HUKUM PIDANA - Juita, Subaidah Ratna; Kridasaksana, Doddy; Triwati, Ani (Universitas Semarang, 2017)
In the criminal justice system to seek penal mediation. based on thoughts associated with ideas of reform of penal law (penal reform). The background of the criminal law reform is based on the idea of protection for victims of crime. For the victims and potential victims of pollution and / or environmental damage required is the existence of a legal device that provides protection coverage. The problem in this research is related to the aspect of legal protection to the victim of environmental crime through alternative of environmental crime case settlement outside court, that is through penal mediation in perspective of criminal law renewal. The research method used in this study is normative juridical, that is by reviewing or analyzing secondary data in the form of main legal material, by understanding the law as a set of rules or norms positive in the legislation system that regulates the victims of environmental crime life. The results show that the need for alternative settlement of environmental crime cases outside the court, as a real form of legal protection for victims of environmental crime. This means that in the perspective of reform of the criminal law, it is necessary to revise the formulation of Article 85 paragraph (2) of Law no. 32 of 2009 on Environmental Protection and Management, which should also be the legal basis for the settlement of TPLH out of court